Nasal necrosis following use of nasal cannula: A case report - Wooyoung Jang; Daniel Nguyen; Joshua Demke (Otolaryngology Case Reports, 2023)
Necrosis to cosmetically vital anatomical regions of the nose like the columella and the ala can occur after prolonged use of nasal cannula in neonatal patients. Nasal injuries following nasal cannula use occur when the nasal cannula providing oxygen to the neonate is placed too tightly. The mechanical stress leads to soft tissue deformation, causing cell death and tissue damage as well as compression of capillaries and ischemia. Here we present a case report of two preterm infants who have sustained columella necrosis, one more severe than the other. In a rare incidence, we see an infratip and supratip lobular and partial bilateral alar defects. Both patients are currently doing well, and reconstruction will take place in 2–3 years when the potential donor site tissue has fully matured.